The Role of Clinical Instructors and Caring Behavior of Nursing Students During Early Clinical Exposure - Izzah Nabila Afnani; Prestasianita Putri (LPPM Universitas dr. Soebandi, 2026)
Introduction: Nursing education integrates theory and clinical practice through Early Clinical Exposure (ECE) to develop professional nurses with caring behavior. A lack of caring can affect patient satisfaction and service quality. Caring behavior can be influenced by Clinical Instructors (CI) as supervisors and mentors in the clinical practice setting. Methods: This study employed a quantitative correlational approach with a cross-sectional design. The population consisted of 205 nursing students undergoing Early Clinical Exposure (ECE), with a sample of 136 respondents selected using a purposive sampling technique. The instruments used were the NSPIC questionnaire to measure the role of Clinical Instructors (CI) and the CBI-24 to assess students’ caring behavior. Data were analyzed using the Spearman rank correlation test Results: The results of the Clinical Instructor (CI) role questionnaire showed that most respondents were in the good category. Similarly, the majority of students’ caring behavior was also classified as good. The Spearman rank test indicated that the p-value < 0.05, with coefficient correlation 0,496. Conclusions: There is a significant relationship between the role of Clinical Instructors (CI) and the caring behavior of nursing students during Early Clinical Exposure (ECE). The role of the Clinical Instructor (CI) can enhance caring behavior by providing motivation to nursing students, especially during ECE. Keywords: Caring, Clinical instructors, Nursing students, Role